تأثير أستخدام تقنية الواقع المعزز على مستوى التحصيل المعرفى لسباحة الزحف على البطن لدى طالبات کلية التربية الرياضية جامعة بنى سويف The effect of using augmented reality technology on the level of cognitive achievement of abdominal crawl swimming among female students of the Faculty of Physical Education, Beni Suef University - ايمان خلف (Beni-Suef University, Faculty of Physical Education, 2022)
" تأثير أستخدام تقنية الواقع المعزز على مستوى التحصيل المعرفى لسباحة الزحف على البطن لدى طالبات کلية التربية الرياضية جامعة بنى سويف"يهدف البحث إلى التعرف على تأثير استخدام تقنية تکنولوجيا الواقع المعزز على تعلم سباحة الزحف على البطن لطالبات کلية التربية الرياضية، وقد استخدم الباحثون المنهج التجريبى بتصميم المجموعتين أحدهما ضابطة والآخري تجريبية على عينة قوامها (40) طالب وتم تقسيمهم بالتساوي علي المجموعتين، وقد إستعان الباحثون بعينة استطلاعية والبالغ عددهم (10) طلاب من داخل مجتمع البحث ومن خارج العينة الأساسية، وقد أسفرت النتائج إلى وجود فروق دالة إحصائية بين مجموعتي البحث ( الضابطة والتجريبية ) في القياس البعدي لصالح المجموعة التجريبية في المستوى المهارى لتعليم سباحة الزحف على البطن، البرنامج المستخدم باستخدام تقنية الواقع المعزز له تأثير واضح بمقارنته بالبرنامج التقليدي في تعلم سباحة الزحف علي البطن، ساهم البرنامج التقليدى بشکل ايجابى في تعلم سباحة الزحف على البطن وذلک بوجود فروق دالة إحصائيا بين القياس القبلى والبعدى للمجموعه (الضابطة) لصالح القياس البعدي. The research aims to identify the effect of using augmented reality technology on learning to crawl on the stomach for female students of the Faculty of Physical Education. The researchers used the experimental approach by designing two groups, one control and the other experimental on a sample of (40) students who were divided equally between the two groups. The researchers used a sample Exploratory, numbering (10) students from within the research community and outside the basic sample, and the results resulted in the presence of statistically significant differences between the two research groups (control and experimental) in the dimensional measurement in favor of the experimental group in the skill level of teaching swimming to crawl on the abdomen, the program used using the technique of Augmented reality has a clear effect compared to the traditional program in learning to crawl swimming, the traditional program contributed positively to learning to crawl swimming, with the presence of statistically significant differences between the pre- and post-measurement of the (control) group in favor of the post-measurement.